Efficacy of a tiered therapy defibrillator system used to treat recurrent ventricular arrhythmias refractory to drugs. Issue 1 (July 1993) - Rankin, A C; Zaim, S; Powell, A; Zaim, B; Brooks, R; McGovern, B A; Garan, H; Ruskin, J N
Abstract : OBJECTIVE–To evaluate an implantable tiered therapy defibrillator system that delivered antitachycardia pacing treatment for slower well tolerated ventricular tachycardias and cardioversion or defibrillation for fast tachycardias or ventricular fibrillation. METHODS–A tiered treatment device (Ventritex Cadence V-100) was implanted in 30 patients with ventricular tachycardia that was refractory to drugs. Efficacy was evaluated by the responses of induced or spontaneous arrhythmias to the treatments delivered. RESULTS–Antitachycardia pacing successfully terminated 80% of episodes of ventricular tachycardia induced by non-invasive programmed stimulation, but acceleration was brought about by pacing in six patients in 10% of episodes. During a follow up of two to 17 (mean seven) months, 18 patients (60%) had recurrence of ventricular arrhythmias. Antitachycardia pacing terminated ventricular tachycardia in 17 of 18 patients in 87% of episodes. Twelve patients received shocks for ventricular tachycardia or fibrillation. Failure of pacing, with subsequent cardioversion, occurred in nine patients (50%) in one or more episodes. Acceleration of tachycardia by pacing occurred in 10 patients in 5% of episodes. Only two of these patients had experienced acceleration of previously induced arrhythmia. Five patients had spontaneous fast ventricular tachycardia or fibrillation treated by cardioversion or defibrillation. Spurious treatment was delivered in nine patients (30%), during atrial fibrillation in five, sinus tachycardia in two, and because of fracture of the sensing lead system in two patients. The retrieval of stored intracardiac electrograms was of clinical value in assessing spurious treatment. CONCLUSIONS–Tiered treatment was effective in terminating recurrent ventricular arrhythmias in these selected patients. Most episodes were treated successfully by pacing, and resistant tachycardias, pacing induced acceleration, or haemodynamically compromising arrhythmias were treated by shocks.